Developing a Framework for Human Capital Disclosure in Corporate Annual Reports: Array - Adelowotan, Michael (The Journal of Accounting and Management, 2020)
This paper presents a framework with some indicative measures and metrics for communication human capital information to the users of Corporate Annual Reports (CARs). The methodology involved in developing this framework revolves around the use content analysis to ascertain the patterns and context of human capital disclosure (HCD) in CARS of 60 out of the top 100 Johannesburg Stock Exchange (JSE) listed companies. This analytical content analysis was undertaken to discover the extent to which disclosures in CARS relate to identified nine human capital content categories and the ninety-one underlying items. The objective is to provide a framework for human capital disclosures in Corporate Annual Reports of listed companies in South Africa. The human capital disclosure framework could be used as a model by companies in South Africa and other emerging economies in HCD in CARs.